1992
DOI: 10.1007/bf00184543
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac natriuretic peptide hormones during artificial cardiac pacemaker stimulation and left heart catheterization

Abstract: Brain natriuretic peptide (BNP) is synthesized and released predominantly in the ventricular myocardium whereas atrial natriuretic peptide (ANP) is produced mainly in the atria. This study evaluated whether artificial pacemaker stimulation or left heart catheterization results in specific changes in BNP and ANP plasma levels. Both BNP and ANP responded sensitively to changes in pacemaker stimulation (single-chamber pacemakers; pacing rates of 72 and 92/min) and during the left heart catheterization procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[35][36][37] Small studies have shown that natriuretic peptides are elevated in patients during pacing. [38][39][40] These changes occur even after short periods of pacing and seem to be more pronounced during VVI (i.e., ventricular inhibited) than DDD pacing. 41 This may be because VVI pacing leads to atrioventricular dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Small studies have shown that natriuretic peptides are elevated in patients during pacing. [38][39][40] These changes occur even after short periods of pacing and seem to be more pronounced during VVI (i.e., ventricular inhibited) than DDD pacing. 41 This may be because VVI pacing leads to atrioventricular dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure BNP level just after procedure. One previous study 11 have shown that BNP increased 1.2 fold after left heart catheterization with coronary artery disease, though few other studies have over thrown this concept showing no specific changes of BNP level before and just after coronary angiography. One study 17 even showed that just after the percutaneous balloon angioplasty BNP level has been reached its peak level, whereas in other study peak level of BNP was achieved 24 hours after balloon angioplasty.…”
Section: Discussionmentioning
confidence: 94%
“…As it is proved that percutaneous coronary intervention by balloon angioplasty and conventional stenting have got early complications like transient myocardial ischaemia or minor myocardial injury, the possible mechanisms of these early complications have been depicted as due to minor vessel trauma, microembolization of plaque micro particles and intravascular friable material, side branch occlusions, coronary dissection, transient abrupt vessel closure and elastic recoil of the lesioned vessel. Several studies 10,11 have shown the change of novel cardiac markers like CKMB and Troponin T or I level after apparently successful balloon angioplasty supporting the fact of procedural minor myocardial injury.…”
Section: Discussionmentioning
confidence: 96%
“…Not surprisingly, ANP and BNP have been reported to be elevated in experimental pacing models of congestive heart failure [28][29][30]. Small studies have shown that natriuretic peptides are elevated in patients during pacing [31][32][33]. The changes occur even after short periods of pacing and seem to be more pronounced during VVI than DDD or AAIR pacing [34][35][36][37][38].…”
Section: Natriuretic Peptides and Pacingmentioning
confidence: 99%